Fama-French Five Factor Model: Systematic Literature Review - Maulana, Yasir; Komarudin, Munir Nur; Tsuraya, Irma (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2025)
This inquiry is to find out, analyze, and integrate existing findings regarding the application and effectiveness of the Fama-French Five Factor Model in various market contexts through a systematic literature review approach. This research methodology uses a qualitative approach through a systematic literature review and bibliometric analysis through VosViewer software, obtained from 27 articles. Based on the literature review results, the Fama-French Five Factor Model has been shown to be superior in explaining asset price anomalies in several markets, such as Australia and South Africa, compared to previous models. However, its effectiveness varies depending on market characteristics, with less consistent results in emerging markets such as Asia, where profitability and investment factors are not always significant. In the context of the Indonesian market, research shows that FF5FM does not always outperform the three-factor model, suggesting that the addition of new factors may not always be relevant in all markets. Keywords: Fama-French Five Factor; Portfolio; Investment; Asset pricing; SLR